Molecular Authentication of the Medicinal Species of Ligusticum (Ligustici Rhizoma et Radix, “Gao-ben”) by Integrating Non-coding Internal Transcribed Spacer 2 (ITS2) and Its Secondary Structure - Liu, Zhen-wen; Gao, Yu-zhen; Zhou, Jing (Frontiers in Plant Science, 2019)
Ligustici Rhizoma et Radix (LReR), an important Chinese medicine known as “Gao-ben,” refers to Ligusticum sinense Oliv. or Ligusticum jeholense Nakai et Kitag. However, a number of other species are commonly sold as “Gao-ben” in the herbal medicine market, which may result in a series of quality control problems and inconsistent therapeutic effects. The “Gao-ben” is commonly sold sliced and dried, making traditional identification methods difficult. Here, the mini barcode ITS2 region was examined on 68 samples representing LReR and 7 potential adulterant or substitute species. The results showed 100% success rates of PCR and sequencing and the existence of a barcoding gap. The neighbor-joining (NJ) tree indicated that all the tested samples could be exactly identified. The ITS2 secondary structure revealed a clear difference between true “Gao-ben” and three adulterant species. We therefore recommend the use of ITS2 as a mini barcode for distinguishing between closely or distantly related plant species that may be used in Chinese medicine.